The innovation effect of dual-class shares: New evidence from US firms - CAO, Xiaping (Institutional Knowledge at Singapore Management University, 2020)
The proliferation of dual-class structures in the US stock market presents a controversial trend since such shares are traditionally deemed to damage governance quality. We study the relationship between 362 firms with dual-class shares and their innovativeness using patent citations from Google Patents over the 1976 through 2006 period. We find dual-class shares have significant innovation effect in high-tech sectors, hard-to-innovate industries, firms with higher external takeover threat and firms heavily dependent on external equity financing. We also document a positive causality relationship between dual-class structures and the quality of innovation. The channel for this causal relationship is the protection mechanism by which managers can take a long-term view. From a policy perspective, regulators should promote a corporate governance system that protects corporate long-term interest for shareholders.